Need-Based Development of Out-Of-School Guidance and Counseling Services to Strengthen Self-Identity of Karang Taruna Youth - Siska Putri Ayu; Maslina; Inayah Ridhayanti Qarimah; A Nurainun Jariah; Aswar; Ryan Hidayat Rafiola (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
This study aims to design a needs-based Out-of-School Guidance and Counseling program to strengthen self-identity and career readiness among members of the “X” Karang Taruna youth organization in Bantaeng Regency. A qualitative case study approach was used. The instruments employed were observation and interviews. The subjects of this study were 30 Karang Taruna members aged 16–25 years. Data analysis was conducted using thematic analysis, which included open coding, thematic grouping, and interpretation of meaning. Data from observations and interviews were transcribed verbatim and then categorized into main themes such as self-confidence, career, and life skills. The research results revealed three main issues: low self-efficacy and anxiety when speaking in public, an unclear career path, and limited life skills. This program comprises three components: Public Speaking Training, Career Planning Guidance, and Life Skills Training, and is proposed as a community-based counseling model to address psychosocial issues in non-formal youth settings.